A TOTAL QUALITY MANANGEMENT APPROACH TO HANDLE VETERINARY HOSPITAL WASTE MANAGEMENT - M. Y. Mustafa; A. A. Anjum (Journal of Animal and Plant Sciences, 2009)
Case study was conducted at Civil Veterinary Hospital Chak-44, which is providing veterinary services in three union councils of tehsil Muridkey, District Sheikhupura. A questionnaire was developed as a tool for collecting information. Exposure of humans to disease-causing pathogens of animal origin can occur via occupational exposure, water, food, air or soil. The animal wastes include faecal material, respiratory secretions, urine, sloughed feathers, fur, skin and internal body organs which contain high concentrations of both human and animal pathogens (disease- causing microorganisms) and upon transmission to humans and animals, these pathogens can cause illness and even death. From the present study, it was concluded that there is lack of education and proper training of veterinarian and para-veterinary staff regarding proper handling and disposal of animal waste.
Keywords: Animal; Management; Pathogen; Veterinary; Waste.